Strategi Toserba Sunan Drajat Paciran Lamongan dalam Menarik Minat Berbelanja Masyarakat - Fi Jaisyi, Muhammad; Musthofa, R. Zainul; Aminah , Siti; Ulum, Miftachul (Al-Muzdahir : Jurnal Ekonomi Syariah, 2024)
The number of modern retailers in the Paciran area, Lamongan indicates that retail business competition in this area is becoming increasingly complex. Therefore, retailers try to design a strategy to take advantage of opportunities appropriately because these strategies play an important role in facing market competition. Retailers have their own strategies and ways related to the market they want to get, so the business strategy of each retailer is required to be able to attract attention and meet the needs and desires of consumers. This research aims to know, analyze and prove the formulation of the problem; 1) What is the strategy carried out by Sunan Drajat Department Store in attracting public shopping interest? 2) What are the factors that cause the high interest of people to shop at Sunan Drajat Department Store?. This type of research uses descriptive qualitative research methods, using primary and secondary data sources obtained through data collection from the observation process, interviews, and documentation. While the data analysis techniques used use data reduction techniques, data presentation, and conclusion drawing. The result of this study is Sunan Drajat Paciran Department Store in attracting public shopping interest by using 5 strategies, namely product strategy, price strategy, promotion strategy, service strategy, and physical facilities. The reason why consumers shop at Sunan Drajat Department Store if sorted from the most prominent reason is the influence of Sunan Drajat, KH. Abdul Ghofur and pesantren, then prices, services, products, promotions, and facilities. This is in accordance with the theory put forward by Utami and Christina Widya in their book Retail Management that the components of the retail mix strategy are products, prices, promotions, services, and physical facilities